2007
DOI: 10.1093/pubmed/fdm064
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacy harm reduction services for drug misusers: national service delivery and professional attitude development over a decade in Scotland

Abstract: More commitment to harm reduction was evident through improved attitudes and increased services. Service delivery has increased more for dispensing services than for needle exchange. Strategies for delivering future needle exchange and substitute dispensing services are required if demand approaches capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 12 publications
1
59
1
Order By: Relevance
“…Matheson et al looked at the change in pharmacists' attitudes toward providing harm reduction services and noted that with increased exposure to IDUs, pharmacists became more positive about working with this population. 22 This study also found that pharmacists were more comfortable providing opioid substitution services than needle exchange programs, as this role is more in line with a pharmacist's involvement in drug therapy. In a study looking at pharmacists' attitudes about providing advice to IDUs on preventing acquisition and transmission of HIV, hepatitis B and hepatitis C infections, pharmacists acknowledged the need for this service and expressed a desire to expand their role in this area.…”
Section: 31mentioning
confidence: 60%
See 1 more Smart Citation
“…Matheson et al looked at the change in pharmacists' attitudes toward providing harm reduction services and noted that with increased exposure to IDUs, pharmacists became more positive about working with this population. 22 This study also found that pharmacists were more comfortable providing opioid substitution services than needle exchange programs, as this role is more in line with a pharmacist's involvement in drug therapy. In a study looking at pharmacists' attitudes about providing advice to IDUs on preventing acquisition and transmission of HIV, hepatitis B and hepatitis C infections, pharmacists acknowledged the need for this service and expressed a desire to expand their role in this area.…”
Section: 31mentioning
confidence: 60%
“…In Scotland, pharmacists have been active in harm reduction by providing needle exchange services to IDUs, and the number of pharmacies and service users involved in these programs has been increasing. 22 Due to rising levels of hepatitis (B and C) and the recognition that pharmacies could be providing more harm reduction services, better payment models and more guidance on needle exchange policy have been introduced for pharmacies. This policy shift is likely one reason for the increased uptake of harm reduction services by pharmacies in Scotland.…”
Section: Current Practices In Harm Reductionmentioning
confidence: 99%
“…Against a background of increasing methadone users, 4 this indicates a considerably higher rate of methadone prescribing by specialist services since 2000.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…In Scotland, the number of methadone users is increasing, 4 with a current estimate of 22 000 people prescribed methadone. 5 There are over 400 drug-related deaths annually.…”
Section: Introductionmentioning
confidence: 99%
“…Those not accessing naloxone through existing services may include pain patients using prescription opioids, in addition to those that choose to avoid services identified for people who use drugs due to concerns such as anonymity. In Scotland and England community pharmacy is already well integrated into the harm reduction provider network, with increasing engagement demonstrated over time (Matheson, Bond, & Tinelli, 2007;Sheridan, Manning, Ridge, Mayet, & Strang, 2007).…”
Section: Introductionmentioning
confidence: 99%